Influence of hesperetin on the pharmacokinetics of diltiazem in rats - Ravindra Babu Pingili, Surya Sandeep Mullapudi, Sridhar Vemulapalli, Naveen Babu Kilaru (Journal of Applied Pharmaceutical Science, 2023)
Cytochrome P-450 3A4 (CYP3A4) and P-GP substrates exhibit poor bioavailability. Diltiazem is a benzothiazepine derivative used in various cardiovascular conditions. It is a heart muscle and blood vessel relaxant that improves blood pumping to the heart and from the heart. It has low bioavailability because it is a substrate of CYP3A4 and P-GP. Hesperetin (a flavanone) inhibited CYP3A4 and P-GP in previous investigations. The major goal of this research was to see how hesperetin affected diltiazem pharmacokinetics (PK) in rats and employing everted intestinal sac. Male Wistar rats were given diltiazem (15 mg/kg) alone or in combination with hesperetin (12.5, 25, and 50 mg/kg) once daily for 15 days to hesperetin-pretreated animals. Blood samples were collected on the 1st day in a single-dose PK study and on the 15th day in multiple-dosage PK studies. In vitro, diltiazem was incubated with rat-everted intestinal sacs in the presence and absence of hesperetin and conventional P-GP blockers. Diltiazem Cmax, area under the curve, and half-life (T1/2) rose two-fold in rats pretreated with Hesperetin compared to the diltiazem control group, although Tmax did not alter significantly. The value of Mean Residence Time increased by 37% to 47%. There has been a significant reduction in clearing and distribution rates. The results of an in vitro study showed that the transport of diltiazem was significantly increased in the presence of hesperetin and standard P-GP inhibitors. The current study found that hesperetin significantly increased diltiazem systemic absorption by inhibiting CYP3A4 and P-GP.
Keywords: Diltiazem, hesperetin, CYP3A4, P-glycoprotein, bioavailability, pharmacokinetics